2014
DOI: 10.1039/c3ra47034b
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent cyclodextrin carriers for a water soluble ZnII pyrazinoporphyrazine octacation with photosensitizer potential

Abstract: A nitro-benzofurazan-triazolyl carboxymethylated beta-cyclodextrin (NBFT-CM beta CyD) and an oligomer of carboxymethyl beta-cyclodextrin (sodium salt), crosslinked with epichlorohydrin and labeled with rhodaminyl groups (p beta CyD-Rh), exhibit very high affinity in aqueous solution for octacationic photosensitizer [(CH3)(8)LZn](8+) neutralized by I- ions (L = tetrakis-2,3-[5,6-di(2-(pyridiniumyl) pyrazino] porphyrazinato dianion). The photosensitizer (PS) forms complexes with 1 : 2 and 2 : 2 CyD: PS stoichiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Phase solubility study It is well known that solubility of lipophilic compounds can be enhanced by adding CDs to the solution [5][6][7][8]. In this connection, the solubilizing capacity of CDs toward I was studied by phase solubility method [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase solubility study It is well known that solubility of lipophilic compounds can be enhanced by adding CDs to the solution [5][6][7][8]. In this connection, the solubilizing capacity of CDs toward I was studied by phase solubility method [13].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the polar exterior of CD allows the complex to interact favorably with water and this process determines the solubility rise. It has been demonstrated that complex formation with CDs can considerably increase the solubility of numerous drugs [4][5][6]. Moreover, the solid dosage forms prepared on the basis of CD inclusion complexes and designed for an oral administration displayed the increased dissolution rate [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation